2011
DOI: 10.1038/cgt.2011.43
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated hypoxia-targeted gene therapy using HSV thymidine kinase and bacterial nitroreductase prodrug-activating genes in vitro and in vivo

Abstract: Hypoxia is an important factor in tumor growth. It is associated with resistance to conventional anticancer treatments. Gene therapy targeting hypoxic tumor cells therefore has the potential to enhance the efficacy of treatment of solid tumors. Transfection of a panel of tumor cell lines with plasmid constructs containing hypoxia-responsive promoter elements from the genes, vascular endothelial growth factor (VEGF) and erythropoietin, linked to the minimal cytomegalovirus (mCMV) or minimal interleukin-2 (mIL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The 5HRE element has previously been used as an enhancer to utilize the hypoxic microenvironment (39). Harvey et al (40) developed a hypoxia-targeted gene therapy strategy using the herpes simplex virus thymidine kinase and bacterial nitroreductase pro-drug-activating genes and showed that 5HRE linked to the CMV minimal promoter could induce optimum luciferase reporter gene expression. In our previous study, gene therapy vectors under the control of 5HRE and a minimal tumor specific promoter also displayed optimal activation at a low oxygen tension in hepatoma and gastric cancer cells (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…The 5HRE element has previously been used as an enhancer to utilize the hypoxic microenvironment (39). Harvey et al (40) developed a hypoxia-targeted gene therapy strategy using the herpes simplex virus thymidine kinase and bacterial nitroreductase pro-drug-activating genes and showed that 5HRE linked to the CMV minimal promoter could induce optimum luciferase reporter gene expression. In our previous study, gene therapy vectors under the control of 5HRE and a minimal tumor specific promoter also displayed optimal activation at a low oxygen tension in hepatoma and gastric cancer cells (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…This is a clear limitation of this method for regenerative research; it is only effective for eliminating proliferating cell populations. However, therapeutically, this has advantages within the realm of chemotherapy [31]. Similarly, this ‘limitation’ could be leveraged to test the plasticity of regenerative responses regarding the relative roles of proliferative and non-proliferative (i.e., transdifferentiation) mechanisms of cell replacement.…”
Section: Cell-specific Ablation Systemsmentioning
confidence: 99%
“…They showed that among various HRE constructs and promoter elements, 5HRE/CMVmp had optimal activation at a low oxygen tension, which is true in the gastrointestinal tract. Harvey et al 21 developed an adenovirus vector for hypoxia-targeted gene therapy using the herpes simplex virus thymidine kinase and bacterial nitroreductase prodrug-activating genes. They showed that 5HRE derived from vascular endothelial growth factor and linked to the CMV minimal promoter could induce optimum luciferase reporter gene expression.…”
Section: Discussionmentioning
confidence: 99%